2016
DOI: 10.1186/s12864-016-2508-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of Gastrodia elata (Orchidaceae) in response to fungus symbiosis to identify gastrodin biosynthesis-related genes

Abstract: BackgroundGastrodia elata Blume (Orchidaceae) is an important Chinese medicine with several functional components. In the life cycle of G. elata, the orchid develops a symbiotic relationship with two compatible mycorrhizal fungi Mycena spp. and Armillaria mellea during seed germination to form vegetative propagation corm and vegetative growth to develop tubers, respectively. Gastrodin (p-hydroxymethylphenol-beta-D-glucoside) is the most important functional component in G. elata, and gastrodin significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 84 publications
(81 reference statements)
0
47
0
Order By: Relevance
“…RNA-illumina sequencing technology has been extensively used for identifying gene expression at a genome-wide scale in many organisms, including non-model plants. The adoption of this technique, especially mRNA sequencing from floral tissues and de novo transcriptome construction (Figure 4), has been performed in several orchid species, with a goal of identifying genes involved in the biosynthesis and/or biosynthetic pathways of floral volatiles [28,110]. Moreover, other strategies include molecular evolutionary analysis tools.…”
Section: Final Remarks and Future Directions For Overcome The Challengesmentioning
confidence: 99%
“…RNA-illumina sequencing technology has been extensively used for identifying gene expression at a genome-wide scale in many organisms, including non-model plants. The adoption of this technique, especially mRNA sequencing from floral tissues and de novo transcriptome construction (Figure 4), has been performed in several orchid species, with a goal of identifying genes involved in the biosynthesis and/or biosynthetic pathways of floral volatiles [28,110]. Moreover, other strategies include molecular evolutionary analysis tools.…”
Section: Final Remarks and Future Directions For Overcome The Challengesmentioning
confidence: 99%
“…For further development and enlargement of tubers, flowering and fruit setting, Armillaria becomes essential for the nutrient supply. It is also noteworthy that G. elata is a well-known Chinese medicinal orchid (Tsai et al 2016). Recently, a number of pharmacological experiments indicated that it had strong potential to combat Alzheimer’s disease, Parkinson’s disease and other neurodegenerative diseases (Manavalan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, "membrane part" (15,180 unigenes [43.72%]) and "cell" (12,907 unigenes [37.18%]) were the most enriched GO terms within the "cellular component" category; A total of 80,140, 79,085, 96,382, and 73,919 unigenes were counted in the RNA-Seq data sets of flower, leaf, stem, and root tissues, of which 10,888, 8128, 7145 and 9085 unigenes with FPKM ≥10 showed high expression, 27,832, 26,890, 26,903 and 21,844 unigenes with FPKM = 1-10 showed medium expression, and 41,420, 44,067, 62,334 and 42,950 unigenes with FPKM ≤1 showed low expression, respectively ( Fig. 3a) [25,26]. The overall expression level of unigenes was the highest in flowers, followed by stems, leaves, and roots ( Fig.…”
Section: Functional Classification and Expressed Overview Of Unigenesmentioning
confidence: 99%